The Role of Microfinance Banks in Financing Agriculture in Yola North Local Government Area, Adamawa State, Nigeria (Global Journal of Science Frontier Research, 2012)
The study examined the role of microfinance banks in financing agriculture in Yola North Local Government Area of Admawa State. Primary data were collected from a total of 100 farmer selected by simple random sampling. Structured questionnaires were the instrument for data collection from the farmers. Simple descriptive statistics such as means and percentages and frequencies were used to analyze the data collected from respondents. Results reveal that, majority (67.11%) of the respondents were males, while 32.8% were females, 44.74% of the respondents were within the age limit of 31 -40 years, 73.68% of the respondents were married, and 85.53% of the farmers had formal education. 60.53 % used the loan for the purpose for which it was collected and 55.26% repaid the loan collected from the Microfinance Bank Yola in (2010). 15.29% of the respondents identified high interest rate on loan acquired from microfinance bank as a major problem, 10.95% identified delay in loan disbursement as their major problem while only 1.18% of the respondents stated that they were not given the loan they applied for. The study recommends that loans for the farmers should be disbursed in good time; banks should reduce the interest rates on agricultural loans. Also, microfinance banks should be encouraged to act as a major lender in financing small scale farmers in the country to meet the food requirement of the teeming population.
Keywords: Microfinance; Loan; Banks; Yola North; Adamawa State The Role of Microfinance Banks in Financing Agriculture in Yola North Local Government Area; Ada